Responsibilities of Individual Guarantor (Personal Guarantee) Declared Bankrupt - Claudia, Ayumi; D. Liman, Padma; Rifai, Aulia (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this research is to find out the liability of individual guarantors who are declared bankrupt. This research is normative juridical law research. The approaches used in this research are the Legislative Approach and the Conceptual Approach. The legal materials that will be used are primary, secondary, and tertiary legal materials. The method of collecting legal materials is carried out by studying documents in obtaining data from laws and regulations and other documents related to the author's problems related to decision Number 212K/Pdt.Sus-Bankrupt/2015. In the Supreme Court Decision Number 212K/Pdt.Sus-Bankrupt/2015, there is an imbalance between theory and practice. The non-implementation of Article 1824 BW in this decision is detrimental to the insurer. The non-implementation of Article 1824 BW in this decision is detrimental to the insurer. In the Deed of the Guarantor, if it is not expressly agreed that the guarantor is willing to go bankrupt if the debtor defaults, then the legal consequences of the guarantor cannot be filed for bankruptcy over the default committed by the debtor.